Ethnic differences in BMI among Dutch adolescents: what is the role of screen-viewing, active commuting to school, and consumption of soft drinks and high-caloric snacks? - Visscher Tommy LS; Kremers Stef PJ; Brug Johannes; Chinapaw Mai JM; Singh Amika S; van Mechelen Willem (BMC, 2009)
Abstract Background The threats posed by the rising prevalence of overweight and obesity on public health have been widely acknowledged. Several population groups, which deserve special attention because of their higher prevalence rates, have been identified. These include adolescents and ethnic sub-groups. The aim of the present study was twofold: (1) to assess ethnic differences in body mass index (BMI) and in behaviours that are related to both energy intake and energy expenditure, and (2) to examine whether these behaviours explain the relationship between ethnicity and BMI. Methods We conducted a cross-sectional data analysis among 957 Dutch adolescents (mean age = 12.7 years). Body height and weight were measured using a standardized protocol. Adolescents completed a questionnaire on screen-viewing behaviour, physical activity, consumption of sugar-containing beverages, and consumption of high-caloric snacks. Results In our study sample 121 adolescents (= 13%) were of Non-Western origin. BMI was significantly higher in Non-Western adolescents (boys: 19.9 kg/m2, SD = 3.0, girls: 20.9 kg/m2, SD = 3.8) compared to Dutch adolescents (boys: 18.4 kg/m2, SD = 2.8, girls: 19.0 kg/m2, SD = 3.0). Our results show that time spent on television viewing, active commuting to school, and consumption of fruit juices partially mediated the association between BMI and ethnicity. Conclusion Behaviours related to both energy expenditure and energy intake may contribute to the ethnic differences in BMI in adolescents and should be considered when tailoring overweight prevention programs to ethnic subpopulations. Trial registration International Standard Randomised Controlled Trial Number ISRCTN87127361